Undesign critical practices at the intersection of art and design - Coombs, Gretchen; McNamara, Andrew; Sade, Gavin (Routledge, 2019)
"Undesign brings together leading artists, designers and theorists working at the intersection of art and design. The text focuses on design practices, and conceptual approaches, which challenge the traditional notion that design should emphasize its utility over aesthetic or other non-functional considerations. This publication brings to light emerging practices that consider the social, political and aesthetic potential of 'undesigning' our complex designed world. In documenting these new developments the book highlights the overlaps with science, engineering, biotechnology and hactivism, which operate at the intersection of art and design."--Provided by publisher
Keywords: Art and design / Philosophy; Architectural design; Architectural drawing; Architecture / Designs and plans / Presentation drawings; Design; Industrial design